2021
DOI: 10.21037/atm-20-7718
|View full text |Cite
|
Sign up to set email alerts
|

Do the positioning variables of the cage contribute to adjacent facet joint degeneration? Radiological and clinical analysis following intervertebral fusion

Abstract: Background: Compared to other risk factors, adjacent facet joint degeneration (AFD) is the main contributor to adjacent segment disease (ASD). The interbody cage may be a potential indirect risk of AFD.This study investigated the correlations among the lumbar sagittal balance parameters, the inter-body cage's intraoperative positioning variables, and adjacent facet joint degeneration following the transforaminal lumbar interbody fusion (TLIF) technique.Methods: Patients who accepted single-level TLIF for sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…Regarding the location of the cage in lumbar fusion, investigators have also conducted clinical and mechanics studies. A previous study [ 29 ] showed a lower cage center was more liable to cause adjacent facet joint degeneration (AFD) following the transforaminal lumbar interbody fusion (TLIF). Yan Liang [ 30 ] advised the cage should be placed in traverse orientation in TLIF.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the location of the cage in lumbar fusion, investigators have also conducted clinical and mechanics studies. A previous study [ 29 ] showed a lower cage center was more liable to cause adjacent facet joint degeneration (AFD) following the transforaminal lumbar interbody fusion (TLIF). Yan Liang [ 30 ] advised the cage should be placed in traverse orientation in TLIF.…”
Section: Discussionmentioning
confidence: 99%
“…Cage parameters were measured as shown in Fig. 2 B, C. Our preliminary study [ 18 ] on how the positioning variables of the cage contribute to adjacent facet joint degeneration showed that the method of measurement of cage parameters (and not explained here).…”
Section: Methodsmentioning
confidence: 99%
“…2B, C. Our preliminary study [18] on how the positioning variables of the cage contribute to adjacent facet joint degeneration showed Fig. 1 Measurement of lumbar sagittal parameters.…”
Section: Measurement Of Implant Parametersmentioning
confidence: 98%
“…Coronal asymmetric intervertebral space was demonstrated by the intervertebral height difference (IHD) between the medial and lateral margin of the indexed intersegmental space (IHD:|RIH-LIH|) (17). Implant parameters included the angle of the upper/lower pedicle screws (Figure 1B), and the horizontal position of cage (%, normalized to endplate size) (18).…”
Section: Radiographic and Clinical Evaluationsmentioning
confidence: 99%
“…Radiographic measurements were performed on X-ray images using a custom-written MATLAB program (MathWorks, Natick, MA, USA) (18). Intraclass correlation coefficient (ICC) was used to evaluate the consistency of pedicle screw-related complications and segmental fusion based on computed tomography (CT) 1 year after surgery between 2 visits.…”
Section: Radiographic and Clinical Evaluationsmentioning
confidence: 99%